Does postoperative non-sedation improve outcomes for patients after head and neck cancer reconstruction?: A STROBE compliant study. Issue 46 (13th November 2020) - Wu, Cho-Han; Yang, Wen-Chi; Wu, Shih-Chi; Chen, Jian-Xun; Lin, Mei-Chen; Chang, Chang-Cheng; Shih, Pin-Keng
Abstract : Abstract: Whether a strategy of postoperative non-sedation produces better outcomes compared with sedation in patients after head and neck reconstruction remains controversial. Therefore, we retrospectively investigated outcomes in 150 of these patients in our institution. Patients with head and neck cancer that received free anterolateral thigh flap were studied retrospectively, and were categorized in terms of their postoperative care into "sedation" and "non-sedation" groups. The related parameters of each patient were collected for analysis. Overall, 150 patients were included (sedation protocol (N = 56) and non-sedation strategy (N = 94)). No significant differences were observed between groups in patient demographics or postoperative outcomes. Significantly shorter durations of mean and median intensive care unit (ICU) length of stay, mechanical ventilation, hospitalization, and operative time were observed in the non-sedation group than in the sedation group. Among all patients, the sedation and flap reopen were the common variables related to prolonged ICU stay, mechanical ventilator duration, and hospitalization. The current study suggested the strategy of postoperative non-sedation is associated with a significant decrease in the duration of mechanical ventilation, ICU length of stay, hospitalization. Regardless of hospital stay, there were no differences in postoperative outcome between 2 groups.